Hyaluronated liposomes containing H2S-releasing doxorubicin are effective against P-glycoprotein-positive/doxorubicin-resistant osteosarcoma cells and xenografts. (1st August 2019) - Gazzano, Elena; Buondonno, Ilaria; Marengo, Alessandro; Rolando, Barbara; Chegaev, Konstantin; Kopecka, Joanna; Saponara, Simona; Sorge, Matteo; Hattinger, Claudia Maria; Gasco, Alberto; Fruttero, Roberta; Brancaccio, Mara; et al.
Abstract: Doxorubicin (dox) is one of the first-line drug in osteosarcoma treatment but its effectiveness is limited by the efflux pump P-glycoprotein (Pgp) and by the onset of cardiotoxicity. We previously demonstrated that synthetic doxs conjugated with a H2 S-releasing moiety (Sdox) were less cardiotoxic and more effective than dox against Pgp-overexpressing osteosarcoma cells. In order to increase the active delivery to tumor cells, we produced hyaluronic acid (HA)-conjugated liposomes containing Sdox (HA-Lsdox), exploiting the abundance of the HA receptor CD44 in osteosarcoma. HA-Lsdox showed favorable drug-release profile and higher toxicity in vitro and in vivo than dox or the FDA-approved liposomal dox Caelyx ® against Pgp-overexpressing osteosarcoma, displaying the same cardiotoxicity profile of Caelyx ® . Differently from dox, HA-Lsdox delivered the drug within the endoplasmic reticulum (ER), inducing protein sulfhydration and ubiquitination, and activating a ER stress pro-apoptotic response mediated by CHOP. HA-Lsdox also sulfhydrated the nascent Pgp in the ER, reducing its activity. We propose HA-Lsdox as an innovative tool noteworthy to be tested in Pgp-overexpressing patients, who are frequently less responsive to standard treatments in which dox is one of the most important drugs. Highlights: Doxorubicin is the most important drug for first-line treatment of osteosarcoma. Doxorubicin resistance in osteosarcoma is mostly mediated by P-glycoprotein. Hyaluronated liposomes containing H2 S-releasing doxorubicin overcome resistance. Such formulations induce a ER-dependent cell death and inhibit P-glycoprotein.